(untitled) (Historia, 2021)
1. Dr . A.J. Boeseken. Slaves and Free Blacks at the Cape 1658-1 700 2. G.C. Olivier. Suid-Afrika se Buitelandse Beleid 3. E.C. Tabler. Pioneers of Natal and Southeastern Africa. 1552-1878 4. J . Burman. The False Bay Stoy 5. D . Irving. The Trail of the Fox, The Life of Field-MarshalErwin Rommel 6. G.G. Iggers. New Directions in European Historiography 7. P . de Klerk. Die Opuoedingstaak van die Vak Geskiedenis 8. A.H. Winquist. Scandinavians and South Africa 9. O.J.O. Ferreira (red.), Krijgsgevangenschap van L.C. Ruijssenaers, 1899-1902 10. A.M. Davey (ed.), Lawrence Richardson Selected Correspondence. 1902-1903 11. H.E.S. Fisher & A.R.J. Jurica (eds.). Documents in English Economic History - England from 1000 to 1760 12. G.R. Elton. Reform and Reformation, England 1509-1558 13. W.A. Speck. Stability and Strife. England 1714-1 760 14. J.A. Brown. South African Art 15. I . C . Neff & C . V . Maggs, Dictionary of Oriental Rugs 16. C . Danziger. Looking at South Africa 17. G.D. Scholtz. Afrikaner Waarheen? 18. J.R. Pole. The Decision for American Independence 19. Collectors’ Society of SA. Antiques in South Africa